1995
DOI: 10.1007/bf00042042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a pea chitinase gene expressed in response to wounding, fungal infection and the elicitor chitosan

Abstract: The fungicidal class I endochitinases (E.C.3.3.1.14, chitinase) are associated with the biochemical defense of plants against potential pathogens. We isolated and sequenced a genomic clone, DAH53, corresponding to a class I basic endochitinase gene in pea, Chi1. The predicted amino acid sequence of this chitinase contains a hydrophobic C-terminal domain similar to the vacuole targeting sequences of class I chitinases isolated from other plants. The pea genome contains one gene corresponding to the chitinase DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 28 publications
(31 reference statements)
1
22
0
2
Order By: Relevance
“…pisi and F. solani f. sp. phaseoli, both strains were able to elicit increased chitinase activity (Mauch, Hadwiger & Boller, 1984) and increased accumulation of class I chitinase transcripts (Chang et al, 1995) with basically identical kinetics. It should be noted however, that Fusarium solani is a soil-borne fungus which, under natural conditions, might not get in contact with seed pods.…”
Section: Plant Defence Genes Are Induced In the Compatible Interactiomentioning
confidence: 88%
See 1 more Smart Citation
“…pisi and F. solani f. sp. phaseoli, both strains were able to elicit increased chitinase activity (Mauch, Hadwiger & Boller, 1984) and increased accumulation of class I chitinase transcripts (Chang et al, 1995) with basically identical kinetics. It should be noted however, that Fusarium solani is a soil-borne fungus which, under natural conditions, might not get in contact with seed pods.…”
Section: Plant Defence Genes Are Induced In the Compatible Interactiomentioning
confidence: 88%
“…When pea roots were inoculated with spores of the pea pathogen F. solani f. sp. pisi, class I chitinase transcripts accumulated rapidly (Chang et al, 1995) but in that study, no data were presented for infection of pea roots with F. solani f. sp. phaseoli.…”
Section: Plant Defence Genes Are Induced In the Compatible Interactiomentioning
confidence: 89%
“…Four Eucalyptus clusters were similar to class I chitinase of Gossypium hirsutum and Arabis holboelli, one cluster was similar to class IIa chitinase of Gossypium hirsutum and another cluster to class IV chitinase of Daucus carota. Class I chitinases are associated with the biochemical defense of plants against potential pathogens (10). Class IIa chitinase is pathogen-induced and, according to Huynh et al (20), this chitinase showed greater antifungal activity when tested in vitro against the growth of Trichoderma reesei, Alternaria solani, and Fusarium oxysporum.…”
Section: Pathogenesis-related Proteins (Pr-proteins)mentioning
confidence: 99%
“…Após incubação em 30 o C por 10 min, a absorbância foi medida a 480 nm (Urbanek et al, 1991) Basse et al (1992) obtiveram pequenos glicopeptídeos a partir da digestão de uma invertase de levedura por α-quimiotripsina, que foram ativos na eliciação de etileno e respostas de atividade de amônia-liases de fenilalanina (PAL) em células cultivadas de tomateiro. Chang et al (1995) verificaram acúmulo de mRNA de uma quitinase de ervilha eliciada por quitosana de Fusarium sp. Bailey (1995) conseguiu purificar uma proteína (22,5 kDa) de filtrado de cultura de Fusarium oxysporum que induziu etileno e necrose em folhas de Erythroxylum coca.…”
Section: Introductionunclassified